THERMO-MECHANICALLY PROCESSED ROLLED WIRE FOR HIGH - V. A. Lutsenko; V. G. Chernichenko; V. G. Lutsenko; I. N. Radjkova (Литьë и металлургия)
It is shown that at twisting of wire of diameter 1,83 mm, produced by direct wire drawing of thermomechanically processed rolled wire of diameter 5,5 mm of steel 90, metal stratification is completely eliminated at decrease of carbon, manganese and an additional alloying of chrome.